Supertetrahedral Networks and Lithium‐Ion Mobility in Li2SiP2 and LiSi2P3. Issue 43 (27th September 2016) - Haffner, Arthur; Bräuniger, Thomas; Johrendt, Dirk
Abstract: The new phosphidosilicates Li2 SiP2 and LiSi2 P3 were synthesized by heating the elements at 1123 K and characterized by single‐crystal X‐ray diffraction. Li2 SiP2 ( I 41 / acd, Z= 32, a= 12.111(1) Å, c= 18.658(2) Å) contains two interpenetrating diamond‐like tetrahedral networks consisting of corner‐sharing T2 supertetrahedra [(SiP4/2 )4 ]. Sphalerite‐like interpenetrating networks of uniquely bridged T4 and T5 supertetrahedra make up the complex structure of LiSi2 P3 ( I 41 / a, Z= 100, a= 18.4757(3) Å, c= 35.0982(6) Å). The lithium ions are located in the open spaces between the supertetrahedra and coordinated by four to six phosphorus atoms. Temperature‐dependent 7 Li solid‐state MAS NMR spectroscopic data indicate high mobility of the Li + ions with low activation energies of 0.10 eV in Li2 SiP2 and 0.07 eV in LiSi2 P3 . Abstract : Mobile Li + ions between supertetrahedra : The phosphidosilicates Li2 SiP2 and LiSi2 P3 form interpenetrating covalent networks of T2 or T4 and T5 supertetrahedra with diamond‐ or sphalerite‐type topologies. 7 Li solid‐state MAS NMR analysis indicates the high mobility of the Li + ions with small activation energies of 0.07–0.10 eV.